Timing of induced volatile emissions in maize seedlings - Turlings, Ted; Lengwiler, Urs; Bernasconi, Marco; Wechsler, Daniel (My University, 1998)
Maize (Zea mays L.) releases specific volatiles in response to herbivory by caterpillars. These volatiles are known to serve as cues for parasitic wasps to locate the herbivores. In the present study the exact time of volatile emission after simulated herbivory (mechanical damage and treatment with caterpillar regurgitant) was measured for seedlings of the cultivars "Ioana Sweet Corn" and "LG11". Odours were collected every 0.5 h for a total of 12 h. Typical "green leaf odours", (Z)-3-hexenal, (E)-2-hexenal, (Z)-hexen-1-ol, and (Z)-3-hexen-1-yl acetate, were emitted immediately upon damage and their amounts dropped rapidly after the first collections. Several of the induced compounds were released within 2 h after treatment, while others (mainly sesquiterpenoids) started to be released after 4 h. The LG11 seedlings emitted several compounds (e.g. beta-myrcene, (Z)-beta-ocimene, benzyl acetate, beta-caryophyllene, (E,E)-alpha-farnesene) that were not detected for Ioana. (E, E)-alpha-farnesene was continuously emitted by LG11 seedlings, even by undamaged plants. Timing of the release of volatile compounds that the two varieties had in common did not differ significantly, with the exception of indole for which the peak production was considerably earlier for LG11. These findings are discussed in the context of biosynthetic pathways and mechanisms involved in induced emissions of plant volatiles and the exploitation of the resulting odour by parasitoids and predators of herbivores.
Keywords: induced defence; parasitoid; plant-insect interactions; semiochemicals; volatiles; Zea mays; PLANT VOLATILES; PARASITIC WASPS; MEVALONOID ORIGIN; CHEMICAL SIGNALS; COTTON PLANTS; HOST LOCATION; BIOSYNTHESIS; ELICITOR; SEMIOCHEMICALS; INFOCHEMICALS